2019
DOI: 10.1101/19012773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aberrant effective connectivity is associated with positive symptoms in first-episode schizophrenia

Abstract: Schizophrenia is a tenacious psychiatric disorder thought to result from synaptic dysfunction. While symptomatology is traditionally divided into positive and negative symptoms, abnormal social cognition is now recognized a key component of schizophrenia. Nonetheless, we are still lacking a mechanistic understanding of how aberrant synaptic connectivity is expressed in schizophrenia during social perception and how it relates to positive and negative symptomatology. We used fMRI and dynamic causal modelling (D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Studies focusing on connectivity analysis could bring further detail to the biological processes underlying these findings, and specific disease trajectories occurring in BPD and SCZ ( Jimenez, 2019 ). Developmental synaptic dysfunction has been proposed as a likely mechanism of psychotic symptoms, and aberrant connectivity to the TPJ, namely the pSTS, has been reported in first-episode SCZ ( Dietz, 2020 ). Models derived from extrinsic and intrinsic connections to the TPJ, personalized for specific dysfunctions found in SCZ and BPD patients, could identify ideal anatomical targets for differential therapeutic neuromodulation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on connectivity analysis could bring further detail to the biological processes underlying these findings, and specific disease trajectories occurring in BPD and SCZ ( Jimenez, 2019 ). Developmental synaptic dysfunction has been proposed as a likely mechanism of psychotic symptoms, and aberrant connectivity to the TPJ, namely the pSTS, has been reported in first-episode SCZ ( Dietz, 2020 ). Models derived from extrinsic and intrinsic connections to the TPJ, personalized for specific dysfunctions found in SCZ and BPD patients, could identify ideal anatomical targets for differential therapeutic neuromodulation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 30 EP participants and 30 aged and gender-matched controls with no family history of mental health disorders were recruited from October 2017 to July 2019. The sample size for adequate power to detect differences in behavior and functional magnetic resonance imaging (fMRI) was based on similar studies examining EP populations [9][10][11][12][13][14]. All participants were 17-25 years old.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…Studies assessing hierarchical interactions between cortical regions in EP have shown that functional changes may occur in the absence of poor performance in simple tasks [9][10][11][12][13][14]. These findings suggest that hierarchical systems only falter under high levels of task difficulty, such as that engendered by stimulus conflict.…”
Section: Introductionmentioning
confidence: 99%